Effects of molidustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor, on sodium dynamics in hypertensive subtotally nephrectomized rats - Anqi Zhang; Daisuke Nakano; Norihiko Morisawa; Kento Kitada; Wararat Kittikulsuth; Asadur Rahman; Takashi Morikawa; Yoshio Konishi; Akira Nishiyama (Elsevier, 2021)
Hypoxia-inducible factor prolyl hydroxylase (HIF-PHD) inhibitors were developed for treatment of renal anemia. Patients applicable for HIF-PHD inhibitor treatment experience complications such as chronic kidney disease, whereby water and electrolyte homeostasis is disrupted. The effects of hypoxia-inducible factor stabilization on salt accumulation in the setting of reduced renal function remain unclear. In the present study, we investigated the effect of a HIF-PHD inhibitor, molidustat, on salt distribution and excretion in rats with subtotal nephrectomy-induced chronic kidney disease. Male Wistar rats were subjected to 5/6 nephrectomy. After confirming blood pressure elevation (>150 mmHg, at 4 weeks after surgery), rats were treated with molidustat. After 1 week of treatment, molidustat did not significantly improve blood cell volume or blood pressure. Distribution of sodium, potassium, and water in skin, carcass, and bone samples was not affected by molidustat. Furthermore, molidustat had no significant effect on urinary sodium excretion or concentration in response to acute oral salt loading (1 g/kg). In conclusion, molidustat did not affect distribution or excretion of salt in rats subjected to a model of nephron loss.